‘We are more alike than different’: Meet Three Youth Pastoralist Participants from the 2026 Vision for Pastoralist Youth Consultation - Spinelli, Madison (CGIAR System Organization, 2022)
In partnership with the Climate Smart Agriculture Youth Network and Procasur, ILRI supported the first in the series of consultations held at Lukenya University in Makueni County, Kenya from 27-29 September 2022, which brought together 28 young pastoralists living and working in Ethiopia, Kenya and Tanzania. Over three days the youth participants shared their knowledge and skills, learned from each other and listened to experts discuss climate change mitigation strategies and adaptations. The consultation was also a space to develop friendships and networks, providing the youth with a stronger voice moving forward. The pinnacle of the event was developing a statement on the future of pastoralism in the face of climate change, addressing the challenges and defining opportunities for future action.